Quasi-steady acoustic response of wall perforations subject to a grazing-bias flow combination - Tonon, D.; Moers, E.M.T.; Hirschberg, A. (Journal of sound and vibration, 2013)
Well known examples of acoustical dampers are the aero-engine liners, the IC-engine exhaust mufflers, and the liners in combustion chambers. These devices comprise wall perforations, responsible for their sound absorbing features. Understanding the effect of the flow on the acoustic properties of a perforation is essential for the design of acoustic dampers. In the present work the effect of a grazing-bias flow combination on the impedance of slit shaped wall perforations is experimentally investigated by means of a multi-microphone impedance tube. Measurements are carried out for perforation geometries relevant for in technical applications. The focus of the experiments is on the low Strouhal number (quasi-steady) behavior. Analytical models of the steady flow and of the low frequency aeroacoustic behavior of a two-dimensional wall perforation are proposed for the case of a bias flow directed from the grazing flow towards the opposite side of the perforated wall. These theoretical results compare favorably with the experiments, when a semi-empirical correction is used to obtain the correct limit for pure bias flow.